First report of Angiostrongylus vasorum in red foxes (Vulpes vulpes) in Serbia - Gavrilović, P.; Todorović, I.; Pavlović, I.; Živulj, A. (Journal of the Hellenic Veterinary Medical Society, 2019)
Angiostrongylosis caused by Angiostrongylus vasorum is an emerging disease in Europe and the red fox (Vulpes vulpes) is considered as a main reservoir species for this parasite. Since there have been no reports of A. vasorum in red foxes in Serbia at the time of carrying out our investigations, the aim of the investigations was to explore the role of red foxes in South Banat (northern Serbia) as reservoirs for A. vasorum. Legally hunted foxes were autopsied in the Veterinary Specialised Institute “Pančevo”. The heart, lungs and pulmonary artery were examined macroscopically for evidence of gross lesions and for the presence of adult specimens of A. vasorum. Impression smears of the changed lung tissue were examined microscopically for the presence of first stage larvae of A. vasorum and histopathological examination was performed on lung samples. Out of 24 examined foxes hunted in different locations, 13 had lesions manifested in the lungs, which were suspected to be indicative of angiostrongylosis. In the majority of the foxes distal parts of the pulmonary lobes were swollen, firm, and discoloured to dark-red, dark-yellow and darkbrown. The characteristic lesions in distal parts of the pulmonary lobes were completely consistent with the presence of adult parasites in the right heart and pulmonary arteries, and with the presence of the first stage larvae in the impression smears. The present finding contributes to the knowledge of geographic distribution of angiostrongylosis in red foxes in Europe and provides valuable information that should raise awareness in veterinarians to consider this parasitosis in dogs with signs of cardiopulmonary diseases.